Autophagy and cytokines - HARRIS, JAMES (My University, 2011)
Autophagy is a highly conserved homoeostatic mechanism for the lysosomal degradation of cytosolic constituents, including long-lived macromolecules, organelles and intracellular pathogens. Autophagosomes are formed in response to a number of environmental stimuli, including amino acid deprivation, but also by both host- and pathogen-derived molecules, including toll-like receptor ligands and cytokines. In particular, IFN-?, TNF-?, IL-1, IL-2, IL-6 and TGF-? have been shown to induce autophagy, while IL-4, IL-10 and IL-13 are inhibitory. Moreover, autophagy can itself regulate the production and secretion of cytokines, including IL-1, IL-18, TNF-?, and Type I IFN. This review discusses the potentially pivotal roles of autophagy in the regulation of inflammation and the coordination of innate and adaptive immune responses.
PUBLISHED
Keywords: Immunology; Infection; Inflammasome; Mycobacteria